English learning strategies among senior high schools in Yogyakarta - Adhi Kusuma; Rahma Dewanti; Regine Aguilar Principe (Universitas Sarjanawiyata Tamansiswa, 2022)
In a Foreign Language setting, the target language is not used widely in the society. It is mostly learnt and used in the classroom contexts. Consequently, learners do not have sufficient language input. As a result, learners are mostly reluctant in using their foreign language which leads to their language acquisition. One of possible strategies lays on the learners themselves in their target language learning strategies. The similar condition fits perfectly to English learners in Indonesia. This research aims to identify the language learning strategies the secondary schools’ students in Yogyakarta. The survey inventory of language learning (SILL) version 7.0 covering six categories’ strategies namely Memory, Cognitive, Compensation, Metacognitive, Affective, and Social is used to investigate the English language learning of the current research participants. The data taken from the secondary schools in Yogyakarta. This study focused on the most frequently used strategy by the secondary school students and describe their difference of strategy in learning the language. From six categories of language learning strategy, there were no strategy used in the high level. As the analysis resulted on the Medium used (M between 2.5 to 3.4). This score indicated that all six of learning strategies are normally used by the students. In addition, the most frequent strategy used by the secondary students is the metacognitive strategy